EphrinB2 signaling in osteoblasts promotes bone mineralization by preventing apoptosis. Issue 10 (30th June 2014) - Tonna, Stephen; Takyar, Farzin M.; Vrahnas, Christina; Crimeen‐Irwin, Blessing; Ho, Patricia W. M.; Poulton, Ingrid J.; Brennan, Holly J.; McGregor, Narelle E.; Allan, Elizabeth H.; Nguyen, Huynh; Forwood, Mark R.; Tatarczuch, Liliana; et al.
Abstract : Cells that form bone (osteoblasts) express both ephrinB2 and EphB4, and previous work has shown that pharmacological inhibition of the eph‐rinB2/EphB4 interaction impairs osteoblast differentiation in vitro and in vivo . The purpose of this study was to determine the role of ephrinB2 signaling in the osteoblast lineage in the process of bone formation. Cultured osteoblasts from mice with osteoblast‐specific ablation of ephrinB2 showed delayed expression of osteoblast differentiation markers, a finding that was reproduced by ephrinB2, but not EphB4, RNA interference. Microcomputed tomography, histomorphometry, and mechanical testing of the mice lacking ephrinB2 in osteoblasts revealed a 2‐fold delay in bone mineralization, a significant reduction in bone stiffness, and a 50% reduction in osteoblast differentiation induced by anabolic parathyroid hormone (PTH) treatment, compared to littermate sex‐ and age‐matched controls. These defects were associated with significantly lower mRNA levels of late osteoblast differentiation markers and greater levels of osteoblast and osteocyte apoptosis, indicated by TUNEL staining and transmission electron microscopy of bone samples, and a 2‐fold increase in annexin V staining and 7‐fold increase in caspase 8 activation in cultured ephrinB2 deficient osteoblasts. We conclude that osteoblast differentiation and bone strength are maintained by antiapoptotic actions of ephrinB2 signaling within the osteoblast lineage.—Tonna, S., Takyar, F. M., Vrahnas, C., Crimeen‐Irwin, B., Ho, P. W. M., Poulton, I. J., Brennan, H. J., McGregor, N. E., Allan, E. H., Nguyen, H., Forwood, M. R., Tatarczuch, L., Mackie, E. J., Martin, T. J., Sims, N. A., EphrinB2 signaling in osteoblasts promotes bone mineralization by preventing apoptosis. FASEB J. 28, 4482–4496 (2014). www.fasebj.org